Increasing Number of Facial Injury in Mangusada General Hospital, Bali: Prevalence and Epidemiology - Tillasman, Natassya Sandra; Mulya, Putu Indri Manikasari; Roosseno, Ratna Rayeni Natasha (Open Access Macedonian Journal of Medical Sciences, 2024)
BACKGROUND: Facial injury has repeatedly been shown to be associated with motor vehicle accident and assaults, which both can be prevented. In Indonesia, motorcycle is the most popular mode of transportation and is accounted for almost 85% of the total registered vehicles in Bali. AIM: This study is aimed to describe the prevalence of facial injury in one of Bali’s Urban Major Trauma Centre to provide documentation for prompt treatment and prevention. METHODS: All the trauma patients who attended the Department of Plastic Surgery, Regional Public Mangusada Hospital, Badung, Bali during the period of 2020–2022 was included in the study. The incidence, prevalence, age, sex distribution and etiology of maxillofacial trauma were studied. The pattern and demographic distribution of fractures of maxillofacial skeleton also were studied. RESULTS: We gathered 495 Facial Injury patients in our centre from January 2020 to December 2022, with significant increase of data every year. We obtained 94 patients in 2020, 136 patients in 2021, and 300 patients in 2022. The result showed that injury involving midfacial regions were the most common (n = 217, 38.9%) with major causative factor was Motor Vehicle Accident comprising 71.1% (n = 352) of all cases. Facial fractures are associated with significant functional, cosmetic, psychological, and socioeconomic effects. Therefore, maxillofacial trauma management requires pertinent documentation. CONCLUSION: The incidence of facial fractures at our center continues to rise annually, highlighting the need for more effective strategies.